Rezygnacja jako przesłanka wygaśnięcia mandatu członka organu spółki kapitałowej: [Resignation as a reason od mandate expiry of a member of Capital company body] (Studia Prawnicze / The Legal Studies, 2007)
Zgodnie z zapowiedzią wskazaną w tytule przedmiotem niniejszych rozważań jest zagadnienie rezygnacji, jako jednej z przesłanek wygaśnięcia mandatu pochodzącego z wyboru członka organu spółki kapitałowej, tj. zarządu, rady nadzorczej, a w spółce z ograniczoną odpowiedzialnością także komisji rewizyjnej. Dywagacje na ten temat będą prowadzone na gruncie odnoszących się do zarządu przepisów prawnych oraz poglądów wyrażanych na ich tle w doktrynie i judykaturze. Podejście takie wynika z tego, że w sprawie wygaśnięcia mandatów członków rady nadzorczej oraz komisji rewizyjnej ustawodawca jedynie odsyła do odpowiedniego stosowania przepisów prawnych dotyczących członków zarządu. Niniejsze opracowanie stanowi próbę wyjaśnienia dwóch kluczowych kwestii związanych z funkcjonowaniem instytucji rezygnacji członka organu z pełnionej funkcji. Pierwszą sprawą jest ustalenie charakteru prawnego zrzeczenia się mandatu, natomiast drugą - ocena dopuszczalności ograniczenia w umowie (statucie) spółki uprawnienia do złożenia rezygnacji, zwłaszcza wówczas, gdy przyczyną ustąpienia z pełnionej funkcji są ważne powody.  Purpose of this article is to clarify two issues related to resignation from the function performed by a member of the Capital company body. The first matter is to establish a legał naturę of resignation from mandate, while the other one - is the assessment of admissibility of restriction on resignation handing in to be contained in company’s articles of association.By presenting the divergent judgements of the Supreme Court and the doctrine opinions, the author is expressing a view that resignation from mandate is a unilateral legał transaction. Not only a lack of prescriptive reąuirement for acceptance of resignation from mandate on the company side speaks for it, but also a elear reference to the regulations of civil codę conceming termination of order by a contractor.Next, while clearing the matter of restriction on possibility of handing resignation in, the author is observing that membership relationship within the body may obtain a naturę of better stability through specification of reasons and term of resignation. The provisions of the company articles in this field may follow two directions: firstly, the parties may restrict the admissibility of resignation making it dependent on occurrence of the specified circumstances; secondly, the company articles of association may set up a term of resignation that is a period with a lapse of which a resignation declaration becomes effective. However, considering the absolutely binding naturę of Article 746 § 3 of the Civil Codę, a member of the body may hand in resignation from performed function at any time by indicating important reasons, which justify his/her decision. On the other hand, if the articles set up the term of resignation, the same shall apply also to the resignation handed in for important reasons.